2005
DOI: 10.1002/ijc.21232
|View full text |Cite
|
Sign up to set email alerts
|

Activating mutations in the extracellular domain of the melanoma inducing receptor Xmrk are tumorigenic in vivo

Abstract: Mutated versions or overexpression of receptor tyrosine kinases such as the epidermal growth factor receptor are found frequently in various cancers. In Xiphophorus the formation of hereditary melanoma is caused by the overexpression of the Xmrk oncogene locus. Xmrk is a mutationally altered version of the epidermal growth factor receptor. Two amino acid changes in the extracellular domain of the receptor were shown in vitro to be responsible for a constitutive, ligand-independent activity of Xmrk. To analyze … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
11
0

Year Published

2006
2006
2019
2019

Publication Types

Select...
5
3

Relationship

3
5

Authors

Journals

citations
Cited by 21 publications
(12 citation statements)
references
References 29 publications
(38 reference statements)
1
11
0
Order By: Relevance
“…(26) In the transgenic fishtumor formation assay, only EGF receptors with either both or one of the two dimerising amino acid changes are tumorigenic, while those without the mutation do not induce cancer. (22,27) The ligand-independent activity of Xmrk is consistent with one of the hallmarks of cancer cells, namely unlimited cell proliferation, which is not controlled by the absence or presence of growth regulating factors. Besides the activating amino acid changes, there is obviously a second precondition for Xmrk-induced melanomagenesis, namely transcriptional activation.…”
Section: Tumor Formation In Xiphophorus Fishmentioning
confidence: 80%
See 1 more Smart Citation
“…(26) In the transgenic fishtumor formation assay, only EGF receptors with either both or one of the two dimerising amino acid changes are tumorigenic, while those without the mutation do not induce cancer. (22,27) The ligand-independent activity of Xmrk is consistent with one of the hallmarks of cancer cells, namely unlimited cell proliferation, which is not controlled by the absence or presence of growth regulating factors. Besides the activating amino acid changes, there is obviously a second precondition for Xmrk-induced melanomagenesis, namely transcriptional activation.…”
Section: Tumor Formation In Xiphophorus Fishmentioning
confidence: 80%
“…Transgenic expression of the platyfish Xmrk gene in the closely related medakafish (Oryzias latipes), which are normally not cancer-prone leads to tumors at high frequency and after short latency periods (22,23) (Wilde, Meierjohann, Laisney and Schartl, unpublished). While the EGF receptor and related growth factor receptor proteins are inactive in the absence of the respective ligand and signal only after the growth factor has bound to the extracellular domain, Xmrk is constitutively active and leads to a ligand-independent activation of the intracellular signal transduction network.…”
Section: Tumor Formation In Xiphophorus Fishmentioning
confidence: 96%
“…However, previous analyses have shown that xmrk is a potent oncogene that can also transform a variety of other cell types (Winkler et al, 1994;Winnemoeller et al, 2005). Owing to this, the generation of a transgenic melanoma model critically depended on a pigment cell-specific promoter to drive xmrk expression.…”
Section: Melanoma Formation In Transgenic Medakamentioning
confidence: 95%
“…Thus, in addition to providing experimental evidence that EGFR activation is biologically relevant, the abovementioned study in the inducible model also points out the possibility that EGFR or its ligands may constitute alternative point(s) of therapeutic intervention in RAS-activated melanoma. It should be mentioned that the contribution of EGFR signaling to melanoma development and possibly progression is evolutionarily conserved, as activating mutations in the EGFR homolog, Xmrk, increase melanoma susceptibility in Xiphophorus fish (Wittbrodt et al 1992;Winnemoeller et al 2005;Meierjohann et al 2006; for review, see Bardeesy et al 2000). It therefore remains possible that similar activating mutations exist in human melanoma, although systematic resequencing of large cohorts of melanomas from different ethnic and/or molecular subclasses will be required to uncover such examples.…”
Section: Receptor Tyrosine Kinase (Rtks) Activationmentioning
confidence: 99%